In vitro experiment on Lactobacillus casei 01 colonizing the digestive system in the presence of pasteurized longan juice - A. Apichartsrangkoon (2018)
© 2015 Akadémiai Kiadó, Budapest. This study was to examine how encapsulated Lactobacillus casei 01 combined with pasteurized longan juice colonized a digestive system by using a simulator of the human intestinal microbial ecosystem. The results showedthat encapsulated L. casei 01 and longan juice stimulated an increase of colon lactobacilli, bifidobacteria, lactic acid and various short-chain fatty acids for which acetate was substantially present in both colons followed by propionateand butyrate. On the contrary, the treatments triggered off the reduction of faecal coliforms, clostridia, and total anaerobes. To sum up, the denaturing-gradient-gel electrophoresis supported that treatment conditions stimulateddiversities of bacteria communities occurring in both colons.